The irony in funeral of two religious sects in Ghana: A comparative study in Islam and Christianity - Bernard, Toffa Akuetey; Adzei, Mawuli; Duhoe, Alberta Aseye Ama (Research Journal in Advanced Humanities, 2020)
This study examines the irony in the two religions, Christian and Islamic with respect to the organization and patronage of funerals in Ghana. Data was collected in four communities across Ghana comprising two Christian and two Moslem communities. This study adopted a collection of both primary and secondary data sources. The primary data was analyzed qualitatively in order to obtain the information on the funeral services conducted in the religions of Islam and Christianity. The study relied on appropriate primary sources. Such primary data was collected at a realistic level through informal conversational interviews, organized individual interviews and focus group interviews (FGIs). Islamic rules prescribe certain guidelines of how Muslims plan for a burial. Most of the particulars of Muslim funeral rites are taken from Prophet Muhammad’s terms. Christian funeral procedures on the other hand are diversified across sects, regions, and cultural heritage. The Christians advocates for the dead to be buried with respect, but does not propose the particulars of funeral services. The study gives the information on the different practices adopted by the Islamic and Christian religions and therefore contributes to the knowledge of research.